Which factors most challenged instructors’ integration of technology in KSA education between 2009 and 2019? A systematic analysis review - Alharbi, Omran; Alshabeb, Abdulrahman M.; Alshammari, Yousef; Almaqrn, Riam K. (Advances in Social Sciences Research Journal, 2020)
The introduction of technologies such as E-learning, Learning Management System (LMS), Twitter, Facebook etc. into teaching and learning practices can make the education environment more attractive and active. However, there are some impediments, both external and internal, that influence the use of this technology. As a result, this study attempts to review and analyse studies that have investigated the important internal and external obstacles to faculty members’ use of technology in Saudi education. This study is a systematic analysis review of the relevant literature published between 2009 and 2019. The methodology adopted was the searching of databases. Many databases were searched in order to find the largest number possible of resources and references. Following the criteria established for collecting this data, 16 studies were finally included in the review. The results indicate that a lack of interests and knowledge, and attitudes are the most common internal elements that affect instructors’ use of technology in the Saudi education context, whereas lack of training and time were mentioned as the most common elements that affect instructors use of technology in Saudi education by previous research. This paper discusses the review findings and makes some recommendations.